Role of Radiotherapy in Management of Choroidal Melanoma: A Review - Shraddha Puranik; Prashant Nathani; Sanjay Kumar Mishra (Delhi Journal of Ophthalmology)
Choroidal melanoma is the most common primary malignant intraocular tumour. Traditional management of choroidal melanoma is enucleation and local resection. Radiotherapy is emerging as an alternative to surgery, salvaging the vision of the patient. The most commonly used mode of radiotherapy is brachytherapy. With Iodine 125 plaque, 50% of the tumours are seen to reduce to 50% of their pretreatment size. External beam irradiation using charged particles such as protons and Helium ions is another option available. Trans-pupillary thermotherapy, Gamma knife therapy and Carbon ion therapy are thought to be the future of treatment of choroidal melanoma.